Amelogenin Localization in Periodontium Healing of Glucocorticosteriod-Induced Osteoporosis in Rabbit - Nada M. H. Al-Ghaban; Nawar Bahjet Kamil; BanA.Ghani Jamil; Bushra Habeeb Al-Maula (Institute of Medico-legal Publications Pvt Ltd, 2022)
Several recent studies had focused on impact of the changes in osteoporosis and its relation to the periodontium healing process. The aim of our present study is to evaluate the effect of osteoporosis on the periodontium healing immunohistochemicaly and on amelogenin. A total of twenty female New Zealand rabbits were assigned randomly into two groups, a ten healthy (control), and an other ten were subjected to a glucocorticoid induce osteoporosis. ligatures were haphazardly placed for the 1st mandibular molars in order to induce periodontitis, then animals had been sacrificed after 4 weeks and the specimens were processed routinely for a serial decalcified sections for the histological and the immunohistochemical study on “ amelogenin”. The histological results of our present study had revealed a delay in the process of healing of periodontium of the experimental group as compared to the control group. The immunohistochemical findings had shown a higher immunoreactivity of the periodontium cells of the osteoporotic groups than the control groups. This study found that the osteoporotic state induced by glucocorticoids may cause a delay in the healing by inducing periodontitis with a mild to moderate immunoreactivity to amelogenin as compared to the control group.